Etiology, Epidemiology, and Therapeutic Approaches for Primary Sclerosing Cholangitis in the Context of Concurrent Non-specific Inflammatory Bowel Diseases - Olszewska, Anna; Matyja, Karolina; Berner, Aleksandra; Stencel, Katarzyna; Stelmaszak, Karina; Marczyk, Klaudia; Polak, Paulina; Pękała, Maciej; Polaszek, Monika; Bogowska, Marta (Journal of Education, Health and Sport, 2024)
Introduction: Primary sclerosing cholangitis (PSC) is a chronic, idiopathic disease characterized by persistent and progressive inflammation of the intrahepatic and/or extrahepatic bile ducts. This leads to fibrosis, cholestatic complications, and liver failure. In over 70% of patients, non-specific intestinal inflammations coexist, particularly ulcerative colitis, and sporadically Crohn's disease. Aim: Our study aimed to assess current literature on primary sclerosing cholangitis (PSC), covering its causes, symptoms, treatment methods, and the connection between PSC and inflammatory bowel disease (IBD) co-occurrence. Materials and methods: We conducted a PubMed literature review using keywords like "primary sclerosing cholangitis pathogenesis," "primary sclerosing cholangitis and inflammatory bowel disease," and "primary sclerosing cholangitis and ulcerative colitis.” Results: Our research extensively covered PSC epidemiology, pathogenesis, and treatment options. Emphasis was placed on the heightened prevalence of inflammatory bowel diseases, including ulcerative colitis, among PSC patients. Summary: Primary sclerosing cholangitis (PSC) is a disease causing gradual damage to bile ducts within or outside the liver. Over 70% of patients also experience inflammatory bowel disease (IBD), mainly ulcerative colitis. The exact causes of PSC and its connection to IBD remain unclear. The theories involve hyperactive "intestinal" T cells or the impact of gut microbiome on their growth. Presently, a liver transplant stands as the sole remedy.